Non‐Redfieldian Dynamics Explain Seasonal pCO2 Drawdown in the Gulf of Bothnia. Issue 1 (10th January 2018) - Fransner, Filippa; Gustafsson, Erik; Tedesco, Letizia; Vichi, Marcello; Hordoir, Robinson; Roquet, Fabien; Spilling, Kristian; Kuznetsov, Ivan; Eilola, Kari; Mörth, Carl‐Magnus; Humborg, Christoph; Nycander, Jonas
Abstract: High inputs of nutrients and organic matter make coastal seas places of intense air‐sea CO2 exchange. Due to their complexity, the role of coastal seas in the global air‐sea CO2 exchange is, however, still uncertain. Here, we investigate the role of phytoplankton stoichiometric flexibility and extracellular DOC production for the seasonal nutrient and CO2 partial pressure (pCO2 ) dynamics in the Gulf of Bothnia, Northern Baltic Sea. A 3‐D ocean biogeochemical‐physical model with variable phytoplankton stoichiometry is for the first time implemented in the area and validated against observations. By simulating non‐Redfieldian internal phytoplankton stoichiometry, and a relatively large production of extracellular dissolved organic carbon (DOC), the model adequately reproduces observed seasonal cycles in macronutrients and pCO2 . The uptake of atmospheric CO2 is underestimated by 50% if instead using the Redfield ratio to determine the carbon assimilation, as in other Baltic Sea models currently in use. The model further suggests, based on the observed drawdown of pCO2, that observational estimates of organic carbon production in the Gulf of Bothnia, derived with the 14 C method, may be heavily underestimated. We conclude that stoichiometric variability and uncoupling of carbon and nutrient assimilation have to be considered in order to better understand the carbon cycle in coastal seas. Key Points: Observed pCO2 and nutrient dynamics are captured by simulating non‐Redfieldian phytoplankton C:N:P ratios and extracellular DOC production The atmospheric CO2 uptake is halved if using the Redfield ratio to determine carbon assimilation The model suggests a more productive Gulf of Bothnia than previous measurements